Review of Islamic Law Against Reconciling Boupah After Triple Divorce - shera yunita (UIN Sunan Gunung Djati, 2023)
This research departs from two sub-districts, namely Sungai Beremas and Koto Balingka, sub-districts related to the reconciliation of a husband and his wife who has been divorced three times. In Islam, Allah regulates everything, including the rules of the permissibility of reconciliation. In triple talaq or Bain Kubra, a man is forbidden to reconcile with his wife unless the wife has remarried someone else and has mixed, then has been divorced, and her iddah period has expired, and then the first husband may marry her return. However, this rule does not apply to some people in Sungai Beremas and Koto Balingka sub-districts. The research method used in this study is a normative approach. The results of the study revealed that referring to boupah after being divorced three times refers to a husband who has divorced his wife three times, by which the husband must pay another man to marry his wife first with certain fees and agreements. The agreement between the two is that the husband and the man who marries his wife promise not to interfere with it and only marry and then divorce her. As for the review of Islamic law regarding the boupah reconciliation event, it is forbidden and considered an act prohibited by religion because it is playing with God's law.